PDRB HIJAU SEKTOR KEHUTANAN HUTAN ALAM KABUPATEN TABALONG DI PROVINSI KALIMANTAN SELATAN - SAVERA ICMI; MUHAMMAD ANSHAR NUR (PPJP Universitas Lambung Mangkurat, 2019)
This study examines the influence of (1) to identify the value of depletion, forest degradation and depreciation Tabalong Regency in South Kalimantan Province (2) can see the value of Forestry Sector Green GRDP Tabalong Regency in South Kalimantan Province. Data is processed using the Green GRDP calculation method. The result of this study prove that the value of the Forestry Sector Green GRDP is smaller than Conventional GRDP. This Green GDRP shows the implementation that Tabalong Regency actually suffered losses due to the exploitation of the forest. The result of the Forestry Sector Green GRDP calculation on 2015 amount to Rp -24,413 milion, in 2016 amount to Rp. -10.816 milion and 2017 amount to Rp28,665 million. Keywords : Depletion, Degredation, Deprication, Conventional GRDP, Forestry Sector Green GRDP.